Characterization of semolina biopolymer films enriched with zinc oxide nano rods - Shima Jafarzadeh (2018)
This research aimed to develop biopolymer-based antimicrobial films as food packaging that will consequently reduce environmental pollution caused by the accumulation of petroleum origin food packaging. Zinc oxide nanorods (ZnO-nr) were incorporated as the antimicrobial component in nanocomposite films based on semolina, which were prepared by solvent casting. SEM and XRD were used to characterize the resulting films. The mechanical, barrier, optical, physical and antimicrobial properties of the films were also analyzed. The addition of ZnO-nr reduced the solubility, WVP, and elongation at break while increased the tensile strength and modulus of elasticity of the nanocomposite films compared with the control film. The apparent surface color and UV transmittance of the semolina films was greatly influenced by the amount of ZnO-nr. The nanocomposite films exhibited 0% UVA in transmittance the near infrared spectra. Furthermore, the ZnO-nr semolina films exhibited strong antimicrobial activity against Staphylococcus aureus.